عملية التجوية والأشكال الأرضية الناتجة عنها في قضاء الدجيل (Journal of the College of Basic Education, 2022)
The sedimentary environment of the study area indicates that it falls within the formation of Anjana. Which is believed to be a river environment that turne into a river continental environment. As for the most important deposits of quaternary time (the era of plastocene) are alluvial fans, gebrite, and sediments of valleys while the deposits of the era of Holocene are floodplains, marshes and deposits formed by humans. As for the surface of the region the lowest point is 28m in the southeastern part of it, and the highest point is82m in the northwest of the region. As for the climate of the study area, it is characterized by drought. Therefore this study came to shed light on the geomorphic processes, represented by weathering and to explain the natural factors that affected them and the resulting earthly shapes in the district of Dujail. the research problem is represented in these questions What are the prevailing weathering operations in the study area? What is the degree of its impact on the formation of earthly shapes? The study aims to define weathering operations.